Effect of extraction method on the antimicrobial activity of Moringa Oleifera seeds extract - Bichi, Mustafa Hassan; Aguwamba, Jonah Chukwu; Muyibi, Suleyman Aremu; Abdulkarim, Mohd Ismail (The Journal of American Science, 2012)
Moringa Oleifera seeds extract has been found to posses antimicrobial properties. The mechanism of its action in this regard is still largely un-determined. In this work, six methods of extracting the active ingredients from the Moringa seed powder were considered. They were: Normal aqueous extraction (M1), Salt extraction (M2), Oil removal followed by aqueous extraction (M3), oil removal followed by salt extraction (M4), oil removal followed by aqueous extraction and microfiltration (M5), and oil removal followed by salt extraction and microfiltration. The antimicrobial action of each extract on Escherichia Coli was determined using Disc Diffusion and Agar Well methods. An average of 639.77±16.72gm of seed kernel was obtained per Kg of raw Moringa seed processed. The results also showed that 72.28±4.84% cake was produced for each 10gm of the <210 μm seed powder de-fatted and the seed oil produced was 28.75±1.68%. The zones of inhibition produced using disc diffusion method ranged 6.5mm – 9.0mm for the six extraction methods with the highest value of 9.0mm obtained with method M3. The Agar well method yielded 6.75mm – 12.38mm zone of inhibition diameter with the highest value of 12.38mm obtained with method M3 of seed extraction. The investigation thus concluded that the M3 was the best extraction method. The Minimum Inhibitory Concentration (MIC) for the Moringa disinfection Solution M3 was determined to be 200μL/mL while the Minimum Bacterial Concentration (MBC) was 210μL/mL. Optimization of the operating conditions was suggested for the subsequent application of this method of seed processing in water disinfection.